Tradition in modern islamic education and the hermeneutics of education in the perspective of Buya Hamka - Febriyani , Febriyani; Suherman, Eman; Noor, Iqbal Hidayatsyah; A.S, Dewi Fatimah Putri (Al-Misbah (Jurnal Islamic Studies), 2024)
This research uses a qualitative approach with the type of research is library research. The data source of this research uses primary data and secondary data. This research aims to find out the thoughts or hermeneutics of education from Buya Hamka's perspective. The results of this study provide answers that through pesantren education, by Buya Hamka regarding his thoughts on modern Islamic education conveys his concept, namely with Aqidah akhlak, without these two components, the quality of education is getting lower, especially in this era of globalization. Therefore, Hamka's thoughts on modern Islamic education are still relevant to be implemented throughout the ages, in order to overcome the current situation through pesantren educational institutions and general educational institutions that do not contradict the existing Islamic tradition so that the Islamic tradition is also not eroded by the existence of modern Islamic education as a fusion of Islamic education with Western education.